DIREITO À MORADIA E A REDE DE PROTEÇÃO SOCIAL: O CASO DAS FAMÍLIAS MONOPARENTAIS FEMININAS NO PROGRAMA “MINHA CASA, MINHA VIDA" EM PONTA GROSSA – ESTADO DO PARANÁ - Oliveira, Rafaella Martins de (2016)
The historical contexts that set the tone for the housing policy in Brazil were quite varied, up until the arrival of the “Minha Casa, Minha Vida” program (“My Home, My Life”, in English), which prioritized families where the woman is responsible for the family unit. This focus correlates historical relations between women, families, social protection networks, and private property, which directly impacted the ways families are formed and configured in Brazil, having a direct effect on the effectivity of public policies regarding housing. In observing this issue, the aim was to comprehend the socioeconomic demands of single-parent families where a woman is the one responsible for the family unit, within the context of the “Minha Casa, Minha Vida” program, “level 1”, in the city of Ponta Grossa, Paraná. In order to seize the topic, it was necessary to undertake an interdisciplinary study, supported by bibliographic and documental research, as well as interviews, developing the research via a qualitative approach with case study. Quantitative data was also utilized, through data gathering with PROLAR (“Housing Company of Ponta Grossa”, in English), which enabled the identification of the socioeconomic profile of the group under analysis – people who expressed their vulnerability and the necessity to have access to housing through the referenced program. The research was deepened by gathering information from the subjects of this process, who were divided into two subgroups in order to be interviewed, aiming to discover their expectations regarding the new housing. Besides families that still wait for the project to deliver, the study also took into consideration people living in five previouslyinstalled housing complexes: Atenas, Boreal, Gralha Azul, Recanto Verde, and Roma. In order to do so, the study was divided into three chapters. The first one deals with the formation of Brazil’s housing policy, showing the influence of the Welfare State and Neoliberalism regarding this issue, up to the implementation of the “Minha Casa, Minha Vida” program.The second chapter pertains to the condition of female-headedsingle-parent families, more specifically the ones in a situation of poverty and social vulnerability, as well as their adaptation to a new logic of the State. Finally, the third chapter sees a characterization of the universe of this study, following the analysis of the interviews. It then became a goal to contribute to the construction of knowledge regarding the network of social protection, especially in relation to female single-parents, considering the State’s performance as the entity responsible for public policies.